Hak-Hak Perempuan Dalam Perspektif Hukum Islam: Kajian Terhadap Kitab Mir'at al-Tullab Syeikh Abdurrauf al-Singkili - Danial (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2022)
Abdurrauf al-Singkili is the mufti of the kingdom of Aceh Darusallam and is also an influential scholar in the archipelago. This research examines the political rights of women in the book Mir'at Al-Tullab by Sheikh Abdurrauf Syiah Kuala. This article is a qualitative study with a descriptive approach. The data used in this study is divided into two, primary data and secondary data. The primary data was obtained from the work of Sheikh Abdulrauf al-Singkili Mir'at al-Tullab fi Tashil Ma'rifat al-Ahkam al-Syar'iyyat li al-Malik al-Wahab, while secondary data was obtained from books, books, journals and articles -Other articles related to the chosen theme. This research shows that Sheikh Abdulrauf al-Singkili in his book considers women's political rights to have no significant differences from men's, women and men have the same rights in politics. Because the texts of the Koran do not explicitly mention the differences between these two creatures, however, he admits that there are certain things that make men the leaders of women.